PENGEMBANGAN AGROWISATA KOPI BERBASIS MASYARAKAT (CBT) DI KAWASAN GUNUNG GALUNGGUNG KABUPATEN TASIKMALAYA - Nurhana Jafaruddin; Trisna Insan Noor; Tuti Karyani (Universitas Galuh Ciamis, 2020)
The tourist area of Mount Galunggung in Tasikmalaya Regency has a tourist attraction for tourists because it has many destinations in one tourist area. Tourist attractions in the tourist area of Mount Galunggung are crater attractions, hot air baths, waterfalls (waterfalls) and Galunggung Shelter coffee shop. The tourism potential of Mount Galunggung is not yet optimal, partly because there is no development of coffee tourism as a tourist attraction that is expected to attract tourists. Therefore all stakeholders must implement the concept of community-based agro-tourism in the Galunggung area. The purpose of this study was to analyze the development of community-based coffee agro-tourism in the Mount Galunggung Tourism Area, Tasikmalaya Regency. Data collection was carried out using a census-based questionnaire. Community Based Tourism (CBT) is a tour that pays attention to culture, social and environment supported by the participation of local communities. Economic, social and environmental aspects are implemented using an average index of perception of the people involved in the development of coffee agro-tourism. Based on the average index the results of the study show that agrotourism is based on economic and environmental aspects in the high category, while social aspects are categorized as very low. Development of community-based agro-tourism can be done by improving aspects that are still not optimal, namely social aspects. Planning for community-based agro-tourism development can be done by improving the social aspects of one through stakeholders by involving the FGD as a whole to discuss which developments have been carried out so that community-based coffee agro-tourism can be developed.